Addressing the Bones: Parades, photography and pedagogy. (4th July 2018) - O'Gorman, Róisín
Abstract : This essay reflects on the Halloween night time community festival, The Dragon of Shandon Parade, on the streets of the Cork (Ireland) led by Cork Community Artlink as a particular iteration of a performative jousting with death. This celebratory event tests the limits of our ability to remember our own deaths and allows for a reflection on the operations of performance and photography as ways to confront and avoid the terrain of death. The essay also considers the process of creating a performance piece for the parade with students from a theatre department alongside encountering human remains with archaeology students. Like the bare bones of archaeological remains, the essay offers a brief evocation of what remains of a performance, a tracing in words and images that intimate a mischievous night on the streets, which in itself offers evocations of myths and stories and the others who have passed by these streets before us. A parade invites not so much a reminder of death, but reminds us of the need to gather together against the petrifying aspects of our fear; we embody those fears with a playful sense of false hubris that will ultimately be quelled, however, for at least one night we move out into to the darkness, put those fears on horseback and ride them out of the town of memory—for now. We can't exactly remember our own deaths but our bones offer us a different kind of remembering, not one of cognition of our individual passing, but a recognition of our passing through this particular time. The formations through time that have left these traces and structures, have given us this feeling in our bones, given us this form by which means we move and from which we will ultimately move on, whether or not we care to remember.